Status and Research Gaps of Microplastics Pollution in Indonesian Waters: A Review - Corry Yanti Manullang; Mufti Petala Patria; Agus Haryono; Sabiqah Tuan Anuar; Suyadi Suyadi; Rafidha Dh Ahmad Opier (Indonesian Journal of Chemistry, 2023)
This study is the first review of current research on microplastics (MPs) in the marine environments at the national scale in Indonesia from 2015 to 2022. This review was conducted to measure the environmental risk and highlight the waste management issue in Indonesian waters. Our literature study found that: (1) the MPs research was mainly conducted in the western part of Indonesia, especially in Java Island; (2) current research has primarily focused on coastal waters (98%) rather than the deep-sea area (2%); (3) the comparability of data is still hampered by difference in quality, about 67% of articles published have not carried out the polymer confirmation; (4) MPs concentrations reported on the articles that did not carry out the polymer identification tended to report higher MPs concentrations. Finally, we propose to have a standard guideline for MPs analysis at a national level and to do more research in the eastern part of Indonesia and deep-sea areas. Further research is required to fill research gaps on plastic distribution and density in deep-sea areas in the eastern part of Indonesia.